Scarification with a Low Concentration of Acid Facilitates Water Acquisition and Minimizes Cold Stratification Duration, Improving the Seed Germination of Canadian Buffaloberry (Shepherdia canadensis (L.) Nutt.) - Sahari Inoue; Jean-Marie Sobze (Seeds)
Canadian buffaloberry (Shepherdia canadensis (L.) Nutt.) is a perennial shrub known for its drought tolerance, nitrogen-fixing ability, and suitability for land reclamation and vegetation, particularly on nutrient-poor industrially disturbed soils in Alberta, Canada. Despite its ecological importance, commercial nurseries and greenhouses face challenges due to limited knowledge of optimizing seed germination and maintaining genetic diversity in cultivated seedlings. In this study, we investigated the interactive effect of cold stratification duration (0, 2, 4, 8, 12, and 16 weeks) and scarification time (control (no scarification), 1, and 4 h) on buffaloberry seed germination. The seed germination rate was tested using a factorial experiment with two factors arranged in a completely randomized design with four replications. Our findings indicate that scarification with a low concentration of acid for 1 h significantly enhances germination outcomes and shortens the required stratification period from 16 weeks to 12 weeks, achieving an optimal germination rate of 82%. Our novel approach using low-concentration acid to scarify Canadian buffaloberry seeds will help commercial greenhouses and forest nurseries improve seed germination, which utilizes this species for land reclamation and reforestation. Furthermore, this method can be adapted to improve germination in other native species with similar dormancy challenges, broadening its applications in ecological restoration efforts.